IMPLEMENTASI MANAJEMEN MUTU TERPADU PENDIDIKAN DI MTs NEGERI 6 BANJAR KECAMATAN MARTAPURA KABUPATEN BANJAR - Mustika Damai Yanti; Zahra’unnisa Aulia (Management of Education: Jurnal Manajemen Pendidikan Islam, 2021)
The background of the problem in this study are 1) The high level ofpublic trust as evidenced by year after year MTs Negeri 6 Banjar is always in demand by the people of Banjar Regency. 2) there are programs excellence that supports the learning process. 3) always improving performance the achievements of MTs Negeri 6 Banjar from year to year. This Researcheraims to describe the implementation of integrated quality management in educationat MTs Negeri 6 Banjar on customer focus, total engagement, measurement, commitment, and continuous improvement. This research usesthe theory of Jerome S. Arcaro. This study uses a descriptive qualitative approach. Data collection is done by conducting interviews, observations, and documentation. Analysis of the data used in this study was carried out by reduce the data, after that it is presented in the form of a description, and verified by conclusion.